Ethnobotanical investigation of medicinal plants used in Lingchuan county, Shanxi, China - Jin,S. (2022)
Abstract Medicinal plants are the primary sources of healthcare among the people of developing countries in villages and local towns. Documenting and reporting the traditional knowledge of medicinal plants may contribute to pharmaceutical research development. For this reason, we present our findings on ethnomedicinal plants from Lingchuan County, Shanxi, China, an unexplored area rich in medicinal plant resources. Information of ethnomedicinal plants were collected through questionnaire/semi-structured interviews from 180 informants, including traditional healers. Field surveys were conducted in 53 villages of Lingchuan County from 2017 to 2018. Informed consent was obtained from each participant before conducting the interview process. Quantitative analysis was performed for each recorded species, such as Relative Frequency Citation (RFC), Use Value (UV), and Factor of Informant Consensus (FIC). Diseases were categorized into twelve groups. A total 138 species of medicinal plants were recorded, belonging to 123 genera of 58 families. Asteraceae was the dominant plant family with 19 species, followed by Rosaceae and Fabaceae. Herbs were dominant among plant life-forms with 96 species, followed by shrubs and trees (15 species each). Roots were the most commonly used plant parts with 58 species, followed by whole plants and fruits (28 species each). Most plant species were reported non-toxic (84, 60%), followed by unknown toxicity (35, 25%), poisonous, and less toxic (19, 14%). Quantitative analysis revealed that Forsythia suspensa was with higher (0.33) RFC value, and Scutellaria baicalensis was recorded with a higher (0.91) UV. Treated diseases were categorized in 12 groups and evaluated by their FIC value, in which gynecological diseases have higher (0.93) FIC value followed by urinary system diseases. Most medicinal plants are used to clear away heat and relieve the surface. The present study revealed that local people of Lingchuan County confidently use ethnomedicinal plants for their healthcare needs. The higher indices value of a plant species resulted from quantitative analysis warrants further investigation, which may possess valuable phytochemical compounds that may result in new drugs for treating various human disorders.